2017
DOI: 10.1590/s1806-92902017000400006
|View full text |Cite
|
Sign up to set email alerts
|

Associations among growth, scrotal circumference, and visual score of beef cattle in performance tests on pasture or in feedlots

Abstract: -This study aimed to evaluate associations among final weight (FW), average daily gain (ADG), scrotal circumference (SC), and visual score (VS) of beef cattle in performance tests on pasture or in feedlots. Genetic parameters for FW, ADG, SC, and VS of young Nellore bulls performance-tested on pasture or in feedlots were evaluated by mixed model. The performance test and final age were considered as fixed effects and additive genetic and residual effects were considered as random effects. Additive genetic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Both the most-positive and the most-negative relationships were observed with calving phenotypes (ejaculate volume and weight of calves, r = 0.0787 ± 0.0003; ejaculate volume and share of normal births, r = −0.0681 ± 0.0003). Other studies found that testis size (e.g., scrotal circumference, length, volume) is genetically correlated with calving interval, ADG, and daughter pregnancy rates (Toelle and Robinson 1985;Meyer et al, 1991;Raidan et al, 2017). However, testis measurements were not available for the BSW bulls considered in our study.…”
Section: = ( )mentioning
confidence: 79%
“…Both the most-positive and the most-negative relationships were observed with calving phenotypes (ejaculate volume and weight of calves, r = 0.0787 ± 0.0003; ejaculate volume and share of normal births, r = −0.0681 ± 0.0003). Other studies found that testis size (e.g., scrotal circumference, length, volume) is genetically correlated with calving interval, ADG, and daughter pregnancy rates (Toelle and Robinson 1985;Meyer et al, 1991;Raidan et al, 2017). However, testis measurements were not available for the BSW bulls considered in our study.…”
Section: = ( )mentioning
confidence: 79%
“…Torres-Júnior and Henry (2005) stated that SC presents favorable genetic correlation with body weight in Guzera animals. Positive genetic correlations among SC, weights, and weight gains at different ages have been described in different studies (Frizzas et al, 2009;Boligon et al, 2010b;Raidan et al, 2017), indicating that these traits are determined, in large proportion, by the action of the same additive genes. The selection for higher scrotal circumferences would lead to increased performance traits.…”
Section: Discussionmentioning
confidence: 92%
“…Discovering how to improve male fertility traits not only has the potential to increase the conception rate but also has the capacity to improve other traits. For example, research shows that selection for increased scrotal circumference (SC) size decreased the calving interval ( Meyer et al, 1991 ), improved daughter pregnancy rates ( Toelle and Robison, 1985 ; Van Melis et al, 2010 ), and increased average daily gain ( Raidan et al, 2016 ). Although it is arguable whether or not SC is an indication of female fertility due to some conflicting results in the literature ( Evans et al, 1999 ; Martínez-Velázquez et al, 2003 ), it is currently the only male fertility-related phenotype collected and utilized for genetic evaluation.…”
Section: Importance Of Male Fertilitymentioning
confidence: 99%